150k views
2 votes
The expression below is a factorization of what trimonial (5x+6)(3x-2)

User Lukew
by
5.6k points

2 Answers

6 votes

Answer:

15x² + 8x - 12

Explanation:

(5x + 6)(3x - 2)

Each term in the second factor is multiplied by each term in the first factor, that is

5x(3x - 2) + 6(3x - 2) ← distribute both parenthesis

= 15x² - 10x + 18x - 12 ← collect like terms

= 15x² + 8x - 12

User Serge Zab
by
6.1k points
1 vote

Answer:


15x^2 + 8x -12

Explanation:

(5x+6)(3x-2)

"foil" it out

F: 5x * 3x = 15x^2

O: 5x * -2 = -10x

I: 6*3x = 18x

L: 6 * -2 = -12

User BrianFinkel
by
5.9k points